A case study of large phytoplankton blooms off the New Jersey coast with multi-sensor observations. (15th September 2015) - Sha, Jin; Jo, Young-Heon; Oliver, Matthew J.; Kohut, Josh T.; Shatley, Matthew; Liu, W. Timothy; Yan, Xiao-Hai
Abstract: Taking the 2011 summer bloom as a study case, we investigated the transport and nutrient delivery mechanisms for large phytoplankton blooms of the New Jersey coast. The horizontal advection of the chlorophyll is approximately one order larger than the horizontal diffusion averaging the whole study area. And the sea surface currents are found to correlate with the wind stress but only for part of the middle shelf. Based on the horizontal advection simulation driven by HF radar current, the bloom is divided into three sub-regions. The northern coastal section of the bloom shows high–low–high pattern in chlorophyll time series, which is related to coastal upwelling and a clockwise eddy. Coastal currents play an important role in the eddy formation and the southward transport of the bloom. The southern coastal section of the bloom is supported by the nutrients from coastal upwelling and driven offshore by wind. The northeast section of the bloom is fueled by nutrient source upwelled through Ekman pumping. The magnitude of Ekman pumping is of the same order as the magnitude of the upwelling along the coast. These identified mechanisms could also applied to more than half of bloom events during 2002 to 2013. In the summer of 2011 off the coast of New Jersey, processes in different sub-regions worked together, leading to this large phytoplankton bloom. Highlights: Coastal upwelling, Ekman pumping and estuary eddies contribute to the bloom. Winds play important roles in transporting and delivering nutrient for bloom growth. The horizontal advection of Chl dominates in the bloom distribution diagnostics. The nutrient delivery mechanisms are applicable to most previous bloom events in this region.